2022
DOI: 10.1037/pla0000159
|View full text |Cite
|
Sign up to set email alerts
|

A case application of Adlerian play therapy with teachers to combat burnout and foster resilience.

Abstract: Students’ achievement is positively correlated with teacher encouragement. This article focuses on the use of Adlerian group play therapy principles and techniques to foster teacher resiliency and reduce burnout. A review of the factors impacting teacher burnout, a description of the practice of Adlerian group play therapy, and the benefits of play techniques with adults will be provided. A case applying Adlerian group play therapy principles and techniques with teachers for the purpose of combating teacher bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…AdPT helps clients obtain a logical understanding of how they view the world, others, and themselves through activities, play, and art. Findings support the importance of AdPT in real-world settings for children (Born & Fenster, 2022). Although the main focus of the first phase of AdPT is building a relationship with the client, the therapist continues to strengthen the relationship throughout all phases of the treatment plan (Kottman, 2011).…”
Section: Alexithymia and Social Isolationsupporting
confidence: 62%
See 4 more Smart Citations
“…AdPT helps clients obtain a logical understanding of how they view the world, others, and themselves through activities, play, and art. Findings support the importance of AdPT in real-world settings for children (Born & Fenster, 2022). Although the main focus of the first phase of AdPT is building a relationship with the client, the therapist continues to strengthen the relationship throughout all phases of the treatment plan (Kottman, 2011).…”
Section: Alexithymia and Social Isolationsupporting
confidence: 62%
“…These findings are consistent with the results of some research. For example, Born and Fenster (2022) suggested that AdPT had a significant improvement in the resiliency of teachers. The sample of this study was teachers, but the sample of the present study was deaf students.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations